Influence of Soil Amendments on Mitigating Methane Emissions and Sustaining Rice Productivity in Paddy Soil Ecosystems of Bangladesh (Journal of Environmental Science and Natural Resources, 2012)
Two field experiments were conducted at two different rice ecosystems, one in the upland rice field of Bangladesh Agricultural University farm, Mymensingh and the another one in the low lying area of Bhaluka, Mymensingh to investigate the effects of soil amendments on mitigation of methane emissions and sustaining rice productivity. The experimental treatments were urea (250 kg ha-1), urea plus coal ash (1t ha-1), urea plus phosphogypsum (90 kg ha-1), urea plus silicate fertilizer (150 kg ha-1), ammonium sulphate 400 kg ha-1, ammonium sulphate plus silicate fertilizer (150 kg ha-1), urea (25% less than the recommended doze) plus cyanobacteria plus azolla (1t ha-1). In case of BAU upland rice field, the total seasonal CH4 emission was decreased by 12-21% and rice grain yield was increased by 4.0- 18.0% respectively, whereas 11.0-26.0% reduction in total CH4 emission and 4.5-24.0% increase in rice grain yield was recorded from the low lying rice field of Bhaluka with the application of soil amendments. Among  the amendments silicate fertilization with urea and silicate in combination with ammonium sulphate reduced total CH4 flux by 18- 23% and 21-26% respectively, whereas rice grain yield was increased by 18-24% and 16-18%, respectively in both ecosystems. Although maximum reduction in total seasonal CH4 flux was recorded with silicate and sulfate of ammonia amendment in paddy soil, however soil acidity was developed which might affect soil fertility and rice productivity in the future. Therefore, silicate fertilizer could be introduced with the nitrogenous fertilizer sources, preferably with 50% urea plus 50% ammonium sulphate for  reducing CH4 emissions and increasing rice productivity under both irrigated upland and lowland rice field ecosystems. DOI: http://dx.doi.org/10.3329/jesnr.v5i1.11574 J. Environ. Sci. & Natural Resources, 5(1): 179 - 185, 2012